Chemical synthesis and characterization of graphene oxide for use as saturable absorber and broadband polarizer / Yap Yuen Kiat - Yap, Yuen Kiat (2015)

(untitled)
Chemically derived graphene oxide (GO) is an atomically thin sheet of graphite that has traditionally served as a precursor for graphene. The tunability of the ratio of its sp2 and sp3 hybridized carbon atoms is a great way to tune its bandgap for different applications. Manipulation of the size, shape and relative fraction of the sp2-hybridized domains of GO enables the tailoring of its optoelectronics properties. This thesis presents works undertaken on the chemical synthesis, characterization and photonics applications of GO. The GO is synthesized using simplified Hummers’ method. The emphasis of the synthesis method is on the experimental time, whereby the long experimental time spent during the oxidation process, typically on mixing the reactants and cooling or heating the reactants have been reduced from 3 – 5 hours to less than 5 minutes. The whole process was carried out without any temperature control, neither increasing nor decreasing the temperature. The mixture was stirred at room temperature for only 3 days and a high degree of oxidation is achieved. Characterization of the area, size, morphology and physical properties of the GO is done using Atomic Force Microscopy (AFM), Field Emission Scanning Electron Microscopy (FESEM), X-ray Diffractometry (XRD), Raman spectroscopy, Fourier Transform Infrared (FTIR) spectroscopy and Thermogravimetric Analysis (TGA). For the nonlinear optical properties of the GO, a set of wide dynamic range power dependent transmission and absorption measurement apparatus and technique are constructed and developed, enabling the determination of some important parameters such as saturation intensity, modulation depth and non-saturable loss. Based on the characterizations, the GO is used as a saturable absorber (SA). The GO was transferred onto a fibre ferrule using ‘dip-coating’ and thin film transfer method. iv Reliable Q-switched fibre lasers were successfully demonstrated. Pulse duration as short as ~4.0 μs and pulse repetition rate of ~60.0 kHz had been achieved. Comparison between GO with reduced graphene oxide (rGO) as a Q-switching device in the same laser resonator was carried out and studied. Finally, to harness the wave-guiding and anisotropic dielectric properties of GO, a broadband waveguide polarizer is realized by coating GO on a polymer optical waveguide. The polarization state of the polarizer output was measured in free space using a polarimeter. The extinction ratio of the GO based polarizer is found to be approximately 40 dB at 1590 nm. This is the highest extinction ratio ever reported for graphene-based waveguide polarizer to date.